Effects of honey on exercise performance and health components: A systematic review - Yusof, A.; Ahmad, N. S.; Hamid M. S. A.; Khong, T. K. (Science & Sports, 2018)
Introduction: Honey consists mainly of carbohydrates (CHO), minerals, and vitamins which are properties that are believed able to improve exercise performance and general health. This review aimed to elucidate findings on the effects of honey on exercise performance as well as combined effects of honey and exercise on health-related outcomes. Methods: Literature was searched systematically based on PRISMA guidelines, using PubMed, Science Direct, SPORTDiscus and Web of Science databases. Thirteen human and animal studies were included in the final analysis. Surprisingly, there were only three randomised-controlled studies that investigated the effect of honey on exercise performance per se, meanwhile, ten reported the combined effects of honey and exercise on bone health, hormones, immune system, and inflammation. Acute honey ingestion improved endurance performance in two studies, while, five studies reported improvements in bone health after consuming honey combined with jumping exercises or aerobic dance. One study reported that stress and reproductive hormones were positively regulated. Five studies reported increase in white blood cells and neutrophils after ingesting honey combined with resistance or aerobic exercises which boosted the immune system. Conclusion: Honey alone could potentially improve aerobic exercise performance; however studies are limited. Meanwhile, honey in combination with exercise promotes bone health and improves immune systems. It is believed that CHO and other constituents of honey play an important role during exercise in exerting the said benefits.